2000
DOI: 10.1021/jp0014059
|View full text |Cite
|
Sign up to set email alerts
|

Six Structures of the Hydrazine Dimer

Abstract: All possible structures of the hydrazine dimer have been investigated in a systematic way for all combinations of the two hydrazine conformers. Three structures with two hydrogen bonds, three with three hydrogen bonds and no structure with only a single hydrogen bond have been found. Two structures with four hydrogen bonds are saddle points of the potential energy surface. In the first step, the geometries of all investigated structures were optimized at the MP2/aug-cc-pVDZ level of theory. In the second step,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 22 publications
5
24
1
Order By: Relevance
“…In contrast, TS g + /c and TS g – /t are sufficiently high in energy, >9 kJ/mol, that interchange between the t and c isomers and the g – and g + isomers is unlikely at room temperature. Finally, we note that TS g – /t is similar to the saddle point found by Dyczmons for the neutral hydrazine dimer …”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In contrast, TS g + /c and TS g – /t are sufficiently high in energy, >9 kJ/mol, that interchange between the t and c isomers and the g – and g + isomers is unlikely at room temperature. Finally, we note that TS g – /t is similar to the saddle point found by Dyczmons for the neutral hydrazine dimer …”
Section: Resultssupporting
confidence: 85%
“…The difference in relative energies from 0 to 298 K is linked to the entropy and extent of hydrogen bonding. As mentioned above, Dyczmons 12 found six conformations for the neutral hydrazine dimer, whereas we locate only four for the proton-bound analogue. This difference is simplistically accounted for by the protonation site, which can only donate a hydrogen bond, restricting the number of isomers.…”
Section: ■ Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…16 with BSSE͒, and Ϫ9.35 ͑Ϫ6.69 with BSSE͒ kcal/mol for the B3LYP/6-31ϩG**, MP2/6-31ϩG**, and MP2/6-311ϩϩG** calculations, respectively͔. In the case of hydrazine 4 both the homochiral and the heterochiral dimers have been calculated, the second one was the most stable by 0.5-0.8 kcal/mol ͓MP2/6-31ϩϩG** and CCSD͑T͔͒ 19 ͑see Table I, 0.5-0.7 kcal/mol͒. This author was not interested in chiral discrimination but IR spectroscopists found that the Sa/Ra dimer of hydrazine explain better the experimental observations than the Sa/Sa(Ra/Ra) dimer.…”
Section: Resultsmentioning
confidence: 97%
“…64 If asso ciation involves the hydrazine hydrogen atoms, this in creases the nucleophilicity of the hydrazine molecule. 64 If asso ciation involves the hydrazine hydrogen atoms, this in creases the nucleophilicity of the hydrazine molecule.…”
Section: Scheme 3 Y = S Sementioning
confidence: 99%